Pengaruh Perbedaan Qirā’āt terhadap Penafsiran Surah Al-Fātiḥah Ayat 4 dalam Literatur Tafsir Klasik dan Kontemporer - Fepriani, Deka; Misnawati (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This article examines the influence of the differences in qirā’āt on the interpretation of surat Al-Fātiḥah verse 4 in classical and contemporary tafsir literature. The focus lies on two main readings “Mālik” and “Malik” both authentic and mutawātir, yet differing in meaning and interpretive impact. Using a library research method, the study analyzes three major sources: Jāmi’ al-Bayān by al-Ṭabarī, Mafātīḥ al-Ghaib by al-Rāzī, and Tafsīr al-Mishbāh by M. Quraish Shihab. The findings reveal that al-Ṭabarī, through his bil ma’tsūr and linguistic approach, favors the reading “Malik” for its semantic strength and contextual coherence with the preceding verse. al-Rāzī, adopting a philosophical approach, does not explicitly favor one reading but considers “Malik” to convey a deeper sense of divine majesty and awe. Meanwhile, Quraish Shihab, with his adabī ijtimā‘ī approach, does not perform tarjīḥ but views both readings as complementary, affirming that Allah is both the Owner and the Sovereign of the Day of Judgment. The differences among these interpretations do not stem from the qirā’āt variations themselves, but rather from the scholars’ distinct intellectual backgrounds, interpretive methodologies, and exegetical orientations in understanding the verse.